1943
DOI: 10.1128/jb.45.3.233-248.1943
|View full text |Cite
|
Sign up to set email alerts
|

Two Antagonistic Fungi, Aspergillus fumigatus and Aspergillus clavatus , and Their Antibiotic Substances

Abstract: It has been definitely established (Waksman, 1941; Waksman and Horning, 1942) that fungi capable of producing anti-bacterial substances are widely distributed in nature and are not limited to any one or more taxonomic groups. Such fungi can be readily isolated from soils, manures, composts, and dust by the use of appropriate bacteria-enriched agar media. Out of some 160 antagonistic fungi thus isolated, two organisms were selected for further study, because of their outstanding capacity to produce in culture m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1944
1944
1998
1998

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(11 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Some isolates of A fumigatus produce a steroid like antibiotic, helvolic acid (Wakeman et al 1943). Aspergillus fumigatus has also been reported as being able to synthesise dicoumarol and 4-hydroxy coumarin in cultures containing o-coumaric acid (Bye et al 1968 ;Bye and King 1970).…”
Section: Storage Derived Mycotoxinsmentioning
confidence: 99%
“…Some isolates of A fumigatus produce a steroid like antibiotic, helvolic acid (Wakeman et al 1943). Aspergillus fumigatus has also been reported as being able to synthesise dicoumarol and 4-hydroxy coumarin in cultures containing o-coumaric acid (Bye et al 1968 ;Bye and King 1970).…”
Section: Storage Derived Mycotoxinsmentioning
confidence: 99%
“…This was confirmed by the observation that the two fractions of gliotoxin obtained from sulfate-containing media contained sulfur whereas the two others did not. The previous findings on the toxicity of fumigacin, as reported by Waksman, Horning and Spencer (1943) and by Robinson (1943) must now be considered in a new light, namely in terms of purified fumigacin, freed from the gliotoxin fraction. Whereas earlier reports indicated that 4 mg of fumigacin injected into 20 gm weight mice by the intraperitoneal method showed evidence of toxicity, the purified fumigacin was tolerated by mice even in concentrations of 16 mg/20 gm.…”
Section: Methodsmentioning
confidence: 79%
“…The method of extraction of fumigacin from the medium was found to have a considerable influence upon the purity of the fumigacin obtained and upon the amount of gliotoxin accompanying it. When the medium is treated by the WHS method (Waksman, Horning, and Spencer, 1943), namely, adsorption on norit, followed by extraction with chloroform, or ether followed by chloroform, only E, limited amount of gliotoxin is found admixed with the fumigacin. However, where the two substances are extracted directly from the medium, using the MWH method (Menzel, Wintersteiner, and Hoogerheide, 1944) a much larger yield of gliotoxin is obtained, the yield of fumigacin remaining, however, practically the same.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sample of processed wild rice that had become damp and moldy through accident was examined by plating out on Czapek solution agar and identifying the isolates. Since the predominating species was found to be A. clavatus, a known Pat producer (16), a composite sample of the moldy rice was extracted and assayed for this toxin by the methods of Pohland and Allen (12). In addition, a typical isolate from the moldy wild rice was tested, along with a known Pat-producing strain, A. clavatus NRRL 1980, as control, for ability to produce Pat.…”
Section: Methodsmentioning
confidence: 99%